Managing Inconsistencies In Software Design Model (International Journal of Scientific Research and Management (IJSRM), 2015)
Design is becoming the important phase of software development because of the demand of quality and complexity of software. One of the greatest challenges to the software engineers and researchers is to identify and resolve the inconsistencies; they meet during a system’s design. If inconsistencies are detected earlier the design phase, mostly problems that might occur during the last stage of software development, can be avoided. Inconsistency is the violation of the rules of software development, the rules must be clearly defined so that one can easily detect the inconsistency and adopt a better solution to resolve it. This research gives a four step inconsistency resolving strategy i.e., to know what the model is? ; To give proper consistency rules in the model?; to explore how the inconsistency happens? and to proposed an effective solution to remove these inconsistencies. The first and second steps include formation of consistency rules using. The rules are applied in the design phase and then classified different violation of these consistency rules by knowing how they can happen. A frame based Inconsistency Management System (FIMS) has been developed that analyse different inconsistencies in the class and the sequence diagram of UML. It also gives a proper solution to handle these inconsistencies.